2009
DOI: 10.1002/jmv.21644
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus core protein enhances Telomerase activity in Huh7 cells

Abstract: Hepatitis C is an oncogenic virus although the mechanisms responsible for this behavior are not clear. We studied the effects of hepatitis C virus (HCV) core protein expression on Telomerase, an enzyme closely associated with cellular immortalization and neoplasia. The aim of this study was to investigate the effects of HCV core protein on the regulation of Telomerase activity in human hepatoma cells. Regulation and expression of human Telomerase reverse transcriptase (TERT) was compared in Huh7 cells stably t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 51 publications
(54 reference statements)
2
28
0
Order By: Relevance
“…Recent data have demonstrated a similar effect of HCV proteins upon telomerase activity. Zhu et al demonstrated a twofold increase in telomerase activity in Huh7 cells expressing HCV core protein compared to mock transfected cells [122]. There were detectable increases in telomerase mRNA, protein, and promoter activity; these changes were associated with significantly longer telomere length in cells expressing HCV core, suggesting functional telomerase activity.…”
Section: Oxidative Stress and Telomeresmentioning
confidence: 95%
“…Recent data have demonstrated a similar effect of HCV proteins upon telomerase activity. Zhu et al demonstrated a twofold increase in telomerase activity in Huh7 cells expressing HCV core protein compared to mock transfected cells [122]. There were detectable increases in telomerase mRNA, protein, and promoter activity; these changes were associated with significantly longer telomere length in cells expressing HCV core, suggesting functional telomerase activity.…”
Section: Oxidative Stress and Telomeresmentioning
confidence: 95%
“…A variety of studies have indicated that telomerase activity is markedly increased either in iron overload or iron deficient condition (Brown et al, 2007;Zhu et al, 2010;Mainous et al, 2013). In human, mutations in TERT have been implicated in predisposing patients to aplastic anemia, a disorder in which the bone marrow fails to produce blood cells (Calado and Young, 2012).…”
Section: The Reduction Of Dntp Poolsmentioning
confidence: 95%
“…TERT-promoter mutations prevent silencing of the TERT gene, increasing its transcription; although TERT-protein expression might not be directly proportional to the level of heightened transcription 157 , even a twofold increase in TERT levels would generate more peptides, potentially making tumour TERT-based immunotherapy. Of relevance, in humans the TERT promoter is a common integration site for several viruses, including hepatitis B virus 153,154 , hepatitis C virus 155 , and human papillomavirus 156 -which can lead to activation of the TERT gene in cis.…”
Section: Box 1 | Issues Relating To the Basic And Applied Science Of mentioning
confidence: 99%